Polymer Thermodynamics Liquid Polymer-Containing Mixtures - Enders, Sabine.; Enders, Sabine.; Wolf, Bernhard A.; Wolf, Bernhard A. (Advances in Polymer Science,, 2011)
Making Flory-Huggins Practical: Thermodynamics of Polymer-Containing Mixtures, by B. A. Wolf * Aqueous Solutions of Polyelectrolytes: Vapor-Liquid Equilibrium and Some Related Properties, by G. Maurer, S. Lammertz, and L. Ninni Schäfer * Gas-Polymer Interactions: Key Thermodynamic Data and Thermophysical Properties, by J.-P. E. Grolier, and S. A.E. Boyer * Interfacial Tension in Binary Polymer Blends and the Effects of Copolymers as Emulsifying Agents, by S. H. Anastasiadis * Theory of Random Copolymer Fractionation in Columns, by Sabine Enders * Computer Simulations and Coarse-Grained Molecular Models Predicting the Equation of State of Polymer Solutions, by K. Binder, B. Mognetti, W. Paul, P. Virnau, and L. Yelash * Modeling of Polymer Phase Equilibria Using Equations of State, by G. Sadowski.